2013
DOI: 10.1007/s00540-013-1751-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of life-threatening hypercapnia with isoflurane in an infant with status asthmaticus

Abstract: We encountered a 2-year-old child with life-threatening hypercapnia, with a PaCO(2) of 238 mm Hg and severe respiratory and metabolic acidosis, due to status asthmaticus that was refractory to steroid and bronchodilator therapy. Suspecting ventilatory failure and excessive ventilation-induced obstructive shock, we started respiratory physiotherapy in synchrony with her respiration, to facilitate exhalation from her over-inflated lungs. Isoflurane inhalation was commenced in preparation for extracorporeal circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The medical literature reports cases of severe hypercapnia in asthmatic patients with values of PaCO 2 reaching 202 and 218 mmHg (pH value, 6.68 and 6.90, respectively) in two 24 and 28 year-old women during severe status asthmaticus [ 12 ], 208 mmHg (pH = 6.73) in a 35 year-old woman during an episode of near fatal asthma [ 13 ] and 175 mmHg (pH = 6.99) in a 33 year-old woman during severe status asthma [ 17 ]. Pediatric reports are scarce, but an eight year-old boy during an episode of near fatal asthma had PaCO 2 values of 293 mmHg (pH = 6.77) [ 14 ], a two year-old girl with status asthmaticus had the values of 238 mmHg (pH = 6.71) [ 16 ] and an eleven year-old boy with status asthmaticus with 187 mmHg and pH of 6.84 [ 15 ].…”
Section: Hypercapnia In Asthmatic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical literature reports cases of severe hypercapnia in asthmatic patients with values of PaCO 2 reaching 202 and 218 mmHg (pH value, 6.68 and 6.90, respectively) in two 24 and 28 year-old women during severe status asthmaticus [ 12 ], 208 mmHg (pH = 6.73) in a 35 year-old woman during an episode of near fatal asthma [ 13 ] and 175 mmHg (pH = 6.99) in a 33 year-old woman during severe status asthma [ 17 ]. Pediatric reports are scarce, but an eight year-old boy during an episode of near fatal asthma had PaCO 2 values of 293 mmHg (pH = 6.77) [ 14 ], a two year-old girl with status asthmaticus had the values of 238 mmHg (pH = 6.71) [ 16 ] and an eleven year-old boy with status asthmaticus with 187 mmHg and pH of 6.84 [ 15 ].…”
Section: Hypercapnia In Asthmatic Patientsmentioning
confidence: 99%
“…Hypercapnia, an elevation in the arterial carbon dioxide (CO 2 ) tension, is a complication of inadequate alveolar gas exchange in patients with severe acute and chronic lung diseases [ 7 ] including asthma [ 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. It has been initially reported that hypercapnia was innocuous or even protective in mechanically ventilated patients with severe asthma [ 9 , 10 ], acute lung injury and acute respiratory distress syndrome (ARDS) [ 18 , 19 , 20 , 21 ], where the concepts of “permissive” and even “therapeutic” hypercapnia have been proposed for the mechanically ventilated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple case reports present successful application of inhaled anesthetics to children and young adults with refractory status asthmaticus, [105][106][107][108][109][110][111][112] but no clinical trials exist comparing this therapy with other adjunct therapies. Retrospective reviews demonstrate that the initiation of these gases is consistently associated with a decrease in P aCO 2 around 20 mm Hg and concomitant rise in pH of about 0.1 within a few hours of administration.…”
Section: Inhaled Anestheticsmentioning
confidence: 99%
“…Retrospective reviews demonstrate that the initiation of these gases is consistently associated with a decrease in P aCO 2 around 20 mm Hg and concomitant rise in pH of about 0.1 within a few hours of administration. 105,108,111,[113][114][115] The largest case series to date includes 31 children over a 15-y period, in which children received isoflurane for a mean duration of 55 h (range 1-181 h) and were invasively ventilated for a mean of 252 h (range 16 -1,444 h). The majority (77%) of these children developed hypotension requiring vasopressor support, but all survived without long-term sequelae.…”
Section: Inhaled Anestheticsmentioning
confidence: 99%